Coumarin-substituted manganese phthalocyanines: synthesis, characterization, photovoltaic behaviour, spectral and electrochemical properties - ÖZKAYA, ALİ RIZA; ALTUN, SELÇUK; ODABAŞ, ZAFER (ROYAL SOC CHEMISTRY, 2014)
The synthesis and spectroscopic characterization of novel manganese(III) phthalocyanines bearing 7-oxy-4-(4-methoxyphenyl)-8-methylcoumarin or/and chloro groups have been achieved. The effect of alpha and beta substitution on the ligand-and metal-based reduction processes of the manganese phthalocyanine complexes and their interaction with dioxygen were investigated. The more effective interaction of the central metal of the beta coumarin substituted complex with dioxygen than that of its alpha substituted analogue was attributed to the hindrance of the interaction by the nonplanarity in the case of alpha substitution. Similarly, the aggregation tendency was lower in the case of alpha substitution. Among the fabricated coumarin-substituted manganese phthalocyanine donor layer and fullerene (C-60) acceptor based photovoltaic heterojunction devices, the one containing 8 exhibited the best performance. The effect of the thickness of the active Pc layer on solar cell parameters has also been investigated. A nearly thickness independent open circuit voltage was observed.
Keywords: OPEN-CIRCUIT VOLTAGE; METAL-FREE; COBALT; COMPLEXES; SPECTROELECTROCHEMISTRY; REDUCTION; CELLS; FILMS